Persepsi Pemuda terhadap Peluang Kerja di Kabupaten Probolinggo - Ira Cahaya Purnama; Putri Raudhatus Sholehah; Dewi Robiatul Munawaroh (PT. Padang Tekno Corp, 2026)
This study aims to analyze youth perceptions of employment opportunities in Probolinggo Regency and identify the factors influencing their decision to work outside their home region. Although Probolinggo Regency possesses considerable economic potential in agriculture, fisheries, plantations, tourism, and small-scale enterprises, many young people still perceive that local employment offers limited career development, income security, and social prestige. This research employed a qualitative approach using a phenomenological method. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that youth migration decisions are influenced by economic considerations, family encouragement, social environment, successful migration experiences of relatives, and expectations of achieving a better quality of life. On the other hand, local economic opportunities remain underutilized due to limited access to information, innovation, and support for youth entrepreneurship. The study suggests that strengthening human resource development, expanding employment information, encouraging youth entrepreneurship, and optimizing local economic potential are essential strategies to increase young people's willingness to pursue careers in their hometowns.